Model Strategy B2B dalam Meningkatkan Consumer Loyalty di Indonesia - Dipa Teruna; Tedy Ardiansyah; Mulawarman Awaloedin (JUDICIOUS, 2022)
The aim of the research is to determine whether consumer loyalty is directly affected by the variables of HR competence, product innovation, and service quality and also to determine the paradigm or model of consumer loyalty to the variables of HR competence, product innovation, and service quality, including the most dominant indicator for each variable. This study was conducted qualitatively, whereas the approach was phenomenological, in which phenomenological studies described people's wisdom in their life experiences. Phenomenologists must pay attention to the existing picture that is owned by all participants when they observe a phenomenon. The sample was taken from five informants who had extensive experience and were currently in the highest positions in a company. The procedure or method used in data processing, assisted by Nvivo12 tools, a special analytical tool in qualitative research that has been recognized worldwide, includes conducting data validation, collecting descriptive data, and forming paradigms. To help answer B2B problems, research instruments draw on previous research and theoretical studies. The results stated that the cluster analysis revealed a strong relationship between statements of opinion from informants regarding B2B policies and consumer loyalty. For map analysis, it was found that all variables affect consumer loyalty and have different indicators, the most dominant of which have a range of 1 to 3 indicators. while simultaneously giving rise to a new variable, namely, a corporate image that supports consumer responsibility. Finally, the B2B model for increasing customer loyalty or consumer loyalty is more prone to service quality and customer loyalty variables.